137Cs and 239+240Pu in the Bohai Sea of China: Comparison in distribution and source identification between the inner bay and the tidal flat. (January 2019) - Zhuang, Qifan; Li, Guosheng; Wang, Fu; Tian, Lizhu; Jiang, Xingyu; Zhang, Kexing; Liu, Geng; Pan, Shaoming; Liu, Zhiyong
Abstract: We investigated artificial radionuclides ( 239+240 Pu and 137 Cs) in surface sediments and sediment cores collected from the Bohai Bay and the tidal flat of the Liaodong Bay, China. Increasing trends for 239+240 Pu activities and 240 Pu/ 239 Pu atom ratios (˃0.18) were observed from land to sea and from north to south in the Bohai Bay. This spatial pattern implied that the scavenging process between riverine sediments and Pacific Proving Ground (PPG) source Pu transported by the currents such as Yellow Sea Warm Current had occurred in the Bohai Bay. In contrast, relatively lower 240 Pu/ 239 Pu atom ratios in the tidal flat of Liaodong Bay were due to the mixing process between more global out and less PPG source Pu. The riverine Pu contributions to the total global fallout Pu in the Haihe River (32.8%) were much lower than those in the Yangtze River estuary (77%–80%), indicating better soil conservation in the Haihe River Catchment. Highlights: Global fallout was the dominant source of Pu to the Bohai Sea. Pacific Proving Ground close-in fallout Pu played a minor role in the Bohai Sea. Pu can be an alternative tracer for studying sedimentation process. The Haihe River input of Pu was estimated to be 2 × 10 11 Bq.